Optimising nutrition of preterm and term infants in the neonatal intensive care unit - Moriam Mustapha (17057997) (2020)
Optimum nutrition leads to improved long-term neurodevelopmental outcomes in both preterm and term infants admitted to the neonatal intensive care (NICU). This review delineates the phases of nutritional management from full parenteral nutrition, transitioning to enteral nutrition and on to full enteral feeds. It describes the essential components of best nutritional care in the neonatal periods and provides practical tips in the management of nutrition in these infants. The authors make recommendations for care based on national and international guidelines and personal expertise of working in a tertiary NICU. Other Information Published in: Paediatrics and Child Health License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.paed.2020.10.008